User-centered design principles in the development of clinical research tools. (December 2020) - Walden, Anita; Garvin, Lynsi; Smerek, Michelle; Johnson, Constance
Background: Increasing and sustaining the engagement of participants in clinical research studies is a goal for clinical investigators, especially for studies that require long-term or frequent involvement of participants. Technology can be used to reduce barriers to participation by providing multiple options for clinical data entry and form submission. However, electronic systems used in clinical research studies should be user-friendly while also ensuring data quality. Directly involving study participants in evaluating the effectiveness and usability of electronic tools may promote wider adoption, maintain involvement, and increase user satisfaction of the technology. While developers of healthcare applications have incorporated user-centered designs, these methods remain uncommon in the design of clinical study tools such as patient-reported outcome surveys or electronic data capture digital health tools. Methods: Our study evaluated whether the clinical research setting may benefit from implementing user-centered design principles. Study participants were recruited to test the web-based form for the Measurement to Understand the Reclassification of Disease of Cabarrus/Kannapolis (MURDOCK) Study Community Translational Population Health Registry and Biorepository that would enable them to complete their study forms electronically. The study enrollment form collects disease history, conditions, smoking status, medications, and other information. The system was initially evaluated by the data management team through traditional user-acceptance testing methods. During the tool evaluation phase, a decision was made to incorporate a small-scale usability study to directly test the system. Results: Results showed that a majority of participants found the system easy to use. Of the eight required tasks, 75% were completed successfully. Of the 72 heuristics violated, language was the most frequent violation. Conclusion: Our study showed that user-centered usability methods can identify important issues and capture information that can enhance the participant's experience and may improve the quality of study tools.